When "More doctors smoked Camels" Cigarette advertising in the journal - Alan Blum (Social Medicine Publication Group, 2024)
Even well into the twentieth century, cigarette smoking hadn't caught on among most men-and definitely not among women. But through mass media advertising and overseas tobacco funds for the boys at war, cigarettes became firmly entrenched by the 1920s. The tobacco companies were the first to offer women equal rights, of a sort, with slogans such as "I'm a Lucky girl," "Blow some my way," and "Do you inhale? Everybody's doing it!" Readers of the Sunday funnies were told by ballplayers like Lou Gehrig and Joe DiMaggio, "They don't get your wind ... So mild, athletes smoke as many as they please!" To respond to those nagging, fuddyduddy health doubters, various salutary claims and endorsements by doctors of certain brands began to appear. By the 1930s cigarette advertisements had made their way into medical journals, including the New York State Journal of Medicine.